Design and Build a Strength Recorder Soil Using Arduino Soil Moisture Sensor - Dony Agam; Alexius Ulan Bani; Fifto Nugroho (Yayasan Bina Internusa Mabarindo, 2022)
Soil strength is one of the important factors for hydrological, biological and chemical processes. Soil strength information is needed for a wide range of government and private sectors related to climate weather, potential runoff and flood control, soil erosion and slope, water resource management, geotechnical engineering and water quality. Soil strength information can also be used for weather prediction, early warning of drought, irrigation scheduling and harvest forecasting. In its application, microcontroller technology will be used which functions as an automatic regulating device to work according to input specifications. In this case, the Arduino Uno microcontroller and the Soil Moisture sensor were selected. The goal is to determine the strength of the soil to prevent landslides and to test the feasibility of the soil for the soil moisture sensor parameter in the soil..